Faktor-Faktor yang Mempengaruhi Frekuensi Pelanggan Berbelanja Produk Fresh Food di Tiara Dewata Denpasar - NOVITA A. P. SILALAHI; DWI P. DARMAWAN; NYOMAN PARINING (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2012)
ABSTRACT Factors Affecting the Frequency of Shopping Customers Fresh Food Products at Tiara Dewata Denpasar The experiment aimed to determine the factors that affect the frequency of customer shopping fresh food products at Tiara Dewata, to find a significant difference between customers who frequently shop and rarely go shopping, to determine what factors most influence the differences in the frequency of customers who frequently shop and rarely buy fresh food products Tiara Dewata. Selection of study sites deliberate. Data analysis method used in this research is the analysis Discriminant were processed using SPSS 13 software for windows. The results showed that there are three variables that affect the frequency of customer shopping fresh food products is support facilities, promotion, and comfort. There are significant differences (real) between groups often shop with a rare group shopping. The difference is that groups often shop has a good assessment of the three variables that affect the frequency of shopping for customers, while the group who rarely shopped have a poor assessment of the three variables that affect the frequency of customer shopping. It can be seen from the above group average values ??are often higher than the average value of the group rarely smaller. The most influential factors are frequency differences shopping facilities to support customers. Keyword: frequency of customer shopping, fresh food products